2020
DOI: 10.1142/s1758825120500362
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Aerodynamic Noise in a Rod-Airfoil Using Suction and Blowing Control Method

Abstract: This paper aims at investigating a two-dimensional flow over the rod-airfoil as a simple component of an aircraft using URANS equations. The prediction of the flow-induced noise is performed using F-WH analogy. Since Vortex’s periodic production is the main cause of the noise mechanism, by reducing its effect on the airfoil leading edge, the acoustic propagation reduces as well. To control flow and reduce noise, in this study, the suction and blowing active control method is employed (blowing in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Szőke [7] found that suction could reduce the trailing edge noise of a flat airfoil. Abbasi et al [8] proved that suction control was also applicable to the flow around the airfoil with the addition of rod interference.…”
Section: Introductionmentioning
confidence: 99%
“…Szőke [7] found that suction could reduce the trailing edge noise of a flat airfoil. Abbasi et al [8] proved that suction control was also applicable to the flow around the airfoil with the addition of rod interference.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on airfoil design and optimization have been conducted to directly decrease the noise emissions by adjusting the aerodynamic shape [1][2][3], such that the suction side of the boundary layer flow perturbation near the trailing edge is suppressed. The boundary layer flow injection/suction treatments at the airfoil trailing edge [4,5] have been investigated, which, combined with a control strategy, showed that a considerate decrease in noise was achieved due to the suppression and alleviation of vortices. Several methods inspired by bionics have been developed, such as serrations applied at the airfoil leading edge and trailing edge [6][7][8] and finlets for rotor noise reduction [9,10], and both add-ons showed good performance in noise reduction by either limiting the magnitude or spanwise correlation length-scale of the turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been conducted in this field, but little research has been done on the effects of using this method on the aerodynamic noise properties. For example, Abbasi and Souri used simultaneous suction and blowing to reduce aerodynamic noise in a rod -airfoil configuration Souri 2020, Abbasi andSouri 2021a). Mathelin et al (2002) experimentally examined the heat transfer around a cylinder containing blowing slot windows.…”
Section: Introductionmentioning
confidence: 99%